2016
DOI: 10.1177/0081246315619833
|View full text |Cite
|
Sign up to set email alerts
|

The role of interpreters in mental health care

Abstract: Increasing globalization and immigration has seen an increase in linguistic and cultural diversity worldwide. This has necessitated the use of interpreters in public service settings. Of particular interest to the authors, and the focus of this article, is the impact of linguistic diversity on access to health care and, more specifically, to mental healthcare services. It is widely documented that language discordance impedes access to, and quality of, health care and that formally trained interpreter-assisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Although previous investigations have examined the association between SLPs’ clinical self-efficacy and years of experience (Harris, 2004; Kimble, 2013), no prior study, to the best of our knowledge, has explored the influence of years of work experience on the decision to utilize or not utilize an interpreter. It is important to note, however, that previous research in other health care fields indicate that only few resident clinicians in nursing (Tuttle, 2009) and recent graduates in mental health (Elkington & Talbot, 2016) access interpreters when compared with experienced clinicians. One possible reason for this difference between newer clinicians and seasoned practitioners could be the limited awareness regarding use of language interpreters among newly qualified SLPs (Elkington & Talbot, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although previous investigations have examined the association between SLPs’ clinical self-efficacy and years of experience (Harris, 2004; Kimble, 2013), no prior study, to the best of our knowledge, has explored the influence of years of work experience on the decision to utilize or not utilize an interpreter. It is important to note, however, that previous research in other health care fields indicate that only few resident clinicians in nursing (Tuttle, 2009) and recent graduates in mental health (Elkington & Talbot, 2016) access interpreters when compared with experienced clinicians. One possible reason for this difference between newer clinicians and seasoned practitioners could be the limited awareness regarding use of language interpreters among newly qualified SLPs (Elkington & Talbot, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…It is important to note, however, that previous research in other health care fields indicate that only few resident clinicians in nursing (Tuttle, 2009) and recent graduates in mental health (Elkington & Talbot, 2016) access interpreters when compared with experienced clinicians. One possible reason for this difference between newer clinicians and seasoned practitioners could be the limited awareness regarding use of language interpreters among newly qualified SLPs (Elkington & Talbot, 2016). It is likely that experienced SLPs have had several opportunities for working with CLD clients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…() however, noted that it was not unusual for a family member or a friend to interpret, or a bilingual health professional to be involved, although misinterpretation as a result of unfamiliar vocabulary or medical terminology was recognised. It has been reported that in some instance parents have used their children, who have adopted the English language, as translators and interpreters, however this practice poses the risk of role reversal which may result in undermining normal lines of communication within families (Elkington & Talbot ; Wood & Newbold ). Adequate interpretation is necessary for the provision of culturally appropriate care.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of democracy in South Africa has brought many benefits, but for the vast majority of people that access public health care there has been no substantial change [3]. Very few mental health care professionals speak an indigenous African language, with Afrikaans and English remaining the dominant languages, and little systematic attention to ethnic differences [6,[34][35][36].…”
Section: The South African Contextmentioning
confidence: 99%